The Quranic Sufism - Mir Valiuddin (Delhi : Motilal Banarsidass Publishers, 2002)
This work explores the foundations of Sufi thought and practice as derived from the Qur an. Mir Valiuddin examines how Qur anic teachings on spirituality, morality, and divine love shaped the development of Sufism, emphasising its roots in Islamic scripture rather than external influences. The book provides both doctrinal insights and historical context to understand Sufism as an authentic expression of Islamic faith.
First published in 1959.
Includes indexes (p. 213-216).
Bibliography: p. 157-212.
Keywords: Qurʼan -- Theology; Sufism; Qur anic studies; Islamic mysticism